Planning interlocked markets and rural development - Hooja, Rakesh (Jaipur, 1990)
The book should greatly interest those involved in rural development and planning-whether as policy makers, planners, administrative change agents, or as academic theory-builders, field researchers, teachers, trainers and students in the various branches of social sciences.
Keywords: Rural development India